Effects of moisture and temperature on Salmonella survivability in beef tallow, white grease, and chicken rendered fat. Issue 3 (22nd June 2021) - Molitor, April; Yucel, Umut; Vipham, Jessie; Jones, Cassandra; Trinetta, Valentina
Abstract: High moisture levels introduced to fats after the rendering process can lead to Salmonella presence and growth. Limited research on strategies to eliminate pathogens in these environments are available. Rendered fat characteristics, such as water activity and fatty acids composition, may contribute to Salmonella survivability. The purpose of this research was to evaluate the effects of moisture levels (0%, 0.5%, 1%, and 3%), storage temperatures (48 and 76 ˚C), and fat characteristics on the growth and survival of Salmonella in beef tallow, white grease and poultry fat samples. Samples were inoculated with a high ( 10 8 CFU/mL) and a low ( 10 5 CFU/mL) Salmonella cocktail ( S . Senftenberg, S . Newport, S . Thompson and S . Infantis). Samples were stored for up to 5 days at 48 and 76 ºC. Remaining population was evaluated daily with and without enrichment step. Death rates were calculated using Weibull model for each temperature and moisture level. Only temperature had an effect ( P < 0.05) on Salmonell a inactivation, while no effect between moisture and/or inoculum level were observed. When all products were challenged at 76 ˚C, counts were below detectable limits after 6 hours. At 48˚C a progressive decline in Salmonella population was observed within 3 days for both beef tallow and white grease when high inoculum was used for the challenge study. Salmonella was below detectable limit within 4 days for both fat types when a low inoculum was instead applied. This research identified the effect of moisture and temperature in rendered fat samples contaminated with Salmonella and underlined the need to use time–moisture–temperature data to minimize microbial growth during transportation and storage.